Purification and characterization of an exo-beta-1,4-glucanase from Ruminococcus flavefaciens FD-1. - Gardner, R M (1987)
An exo-beta-1,4-glucanase (Exo A) from Ruminococcus flavefaciens FD-1 was purified to homogeneity and characterized. Enzyme activity was monitored during purification by using the substrate p-nitrophenyl-beta-D-cellobioside (NPC). Over 85% of the NPC activity was found to be extracellular once the filter paper was degraded (7 days). Culture supernatant was harvested, and the protein was concentrated by ultrafiltration. The retentate (greater than or equal to 300,000 Mr), containing most of the activity against NPC, was then fractionated with a TSK DEAE-5PW column. This yielded a sharp major peak of NPC enzyme activity, followed by a broader, less active area that appeared to contain at least six minor peaks of lower enzymatic activity. Further purification was achieved by chromatography with a hydroxylapatite column. Finally, gel filtration chromatography yielded a homogeneous enzyme (Exo A) as determined by silver stains of both sodium dodecyl sulfate- and nondenaturing electrophoresis gels. Substrate specificity experiments and the products of cellulose digestion indicate that the enzyme was an exo-beta-1,4-glucanase. Exo A required Ca2+ for maximal activity and had an apparent Km of 3.08 mM for NPC, with a Vmax of 0.298 mumol/min per mg of protein. The enzyme had an Mr of 230,000, as determined by gel filtration chromatography, and was a dimer of 118,000-Mr subunits. The N-terminal amino acid sequence of the enzyme is presented.